3D welding and milling: Part I - a direct approach for freeform fabrication of metallic prototypes - Song, YA; Park, S; Choi, D; Jee, H (ELSEVIER SCI LTD, 2005)
Solid Freeform Fabrication (SFF) gives engineers a new freedom to build parts that have thus far proved difficult to manufacture using conventional machining. However, the surface finish and accuracy of SFF parts are lower than those of conventionally machined parts. A process combination of additive and subtractive techniques is currently being developed in order to overcome this problem. A novel hybrid approach of our group called '3D welding and milling' uses gas metal arc welding as an additive and milling as a subtractive technique, thereby exploiting the advantages of both processes. Compared to other deposition processes, gas metal arc welding is the most economic way of depositing metals. In this paper, the initial results of the process development and the characterization of the parts fabricated by this process are reported. (c) 2004 Elsevier Ltd. All rights reserved.